PENGARUH KEPRIBADIAN, KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN PT.PATRA SK - Imran Ramdani (JURNAL LENTERA BISNIS, 2012)
This research aims to analyse and find out 1)The influence of personality, organizational commitment and job satisfaction on employee organizational citizenship behavior (OCB), 2) The personality influence on employee organizational commitment; 3) The personality influence on employee job satisfaction, and 4) The influence of employee job satisfaction on employee organizational commitment. The experiment was conducted in a joint venture company of PT.Pertamina Persero and SK Energy International of Korea, namely PT PATRA SK.The method of analysis used the method of statistical analysis of quantitative and associative hypotheses with cross sectional survey design to investigate the correlation effects of exogenous variables: personality profiles and endogenous variables: OCB, organizational commitment and job satisfaction. Sampling method is simple random sampling of 104 people so the number of employee population sample of respondents used in this study as many as 80 people with 95% degree of confidence. Data were collected with questionnaires that have been tested for validity and reliability by using alpha cronbach formula and the correlation Pearson product moment formula. Scoring statement items is in the questionnaire using 5 point Likert scale. Hypothesis testing research conducted by path analysisThe results of this study show empirically: (1) Personality, organizational commitment, and employee job satisfaction in PT.PATRA SK has positive and significant impact on OCB (r = 0.580, p = 0.000 <0.05, r = 0.201, p = 0.009 <0.05, and r = 0.213, p = 0.002 <0.05), (2) Personality and significant positive effect on organizational commitment (r = 0.699, p = 0.000 <0.05), (3) Personality positive effect and significantly on job satisfaction (r = 0.885, p = 0.000 <0.05), and (4) Job satisfaction and significant positive effect on organizational commitment (r = 0.241, p = 0.011 <0.05). Keywords:             organizational citizenship behavior, job satisfaction, organizational commitment, personality, path analysis.